2014
DOI: 10.3892/mmr.2014.1963
|View full text |Cite
|
Sign up to set email alerts
|

Genetically modified Schwann cells producing glial cell line-derived neurotrophic factor inhibit neuronal apoptosis in rat spinal cord injury

Abstract: Schwann cells (SCs) are the major cells constituting the peripheral nerve structure and function, and also secret a variety of neurotrophic factors. Schwann cell (SC) transplantation has recently emerged as a promising therapeutic strategy for spinal cord injury (SCI). In the present study, the ability of genetically modified SCs producing high levels of glial cell line‑derived neurotrophic factor (GDNF) to promote spinal cord repair was assessed. The GDNF gene was transduced into SCs. The engineered SCs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The combination of GDNF‐SCs improved axonal regeneration beyond SCs alone, which supports other studies (Deng et al, ; Kanno et al, ). GDNF‐SCs have a direct neuroprotective effect on spinal motor neuron survival by inhibiting apoptosis following injury (Liu et al, ). GDNF promotes spinal motor neuron axonal extension (Bohn, ), targeting and synaptic remodeling (Keller‐Peck et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of GDNF‐SCs improved axonal regeneration beyond SCs alone, which supports other studies (Deng et al, ; Kanno et al, ). GDNF‐SCs have a direct neuroprotective effect on spinal motor neuron survival by inhibiting apoptosis following injury (Liu et al, ). GDNF promotes spinal motor neuron axonal extension (Bohn, ), targeting and synaptic remodeling (Keller‐Peck et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Native human UCB-MCs can differentiate into endothelial and microglial cells and UCB-MCs transfected with plasmid vectors that concurrently expressed VEGF and NCAM-L1 showed considerable potential to differentiate into endothelial cells; moreover, UCB-MCs overexpressing VEGF and FGF2 transformed into astrocyte-like S100 + cells and Oct4-Sox2 transfected UCB-MCs expressed the neuronal marker PGP9.5. 26 Studies conducted using various approaches to deliver the GDNF gene have increasingly focused on examining the functional deficits and the preservation of the gray matter of the spinal cord, but these studies have primarily examined the survival of neurons 10,13,27,28 and have mostly ignored the changes in glial cells. Therefore, in this study, we paid particular attention to the effects of direct and cell-mediated delivery of the GDNF gene on the phenotypic and quantitative characteristics of glial cells in the injured spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…GDNF inhibited cell apoptosis on day 28, which was consistent with previous reports. 57,61 Interestingly, the inhibition of cell apoptosis by GDNF was accompanied by the decreased expression of autophagy-induced proteins (Beclin-1, LC3), suggesting that GDNF could protect neural cells against cell death by inhibiting autophagy-induced apoptosis (Fig. 5B,C).…”
Section: Discussionmentioning
confidence: 94%
“…These findings suggest that HP hydrogels may have an important role in recovering the injured spinal cord, probably due to its LMWH. A recent study showed that LMWH can protect against lipopolysaccharide‐induced cognitive impairments by attenuating microglial activation, cytokine release, oxidative stress and loss of synaptic plasticity . Taken together, the efficient cellular uptake, controlled release behavior and LMWH bioactivity of HP hydrogels may contribute to enhance the effects of GDNF on neuronal circuit remodeling and neuroprotection in SCI.…”
Section: Discussionmentioning
confidence: 99%